2011
DOI: 10.1002/jso.22005
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of intratumoral regulatory T cells by human gastric cancer cells is dependent on transforming growth factor‐β1

Abstract: The proportion of functional Treg is elevated in human gastric cancer and related to poor prognosis. Gastric cancer cells directly convert CD4(+) naive T cells to Treg by TGF-β1, suggesting a possible mechanism through which tumor cells evade the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
(39 reference statements)
1
19
0
Order By: Relevance
“…Our study confirmed that Treg density correlated with adverse prognosis, consistent with earlier studies (Kono et al , 2006; Lu et al , 2011; Tao et al , 2012a). However, FoxP3-positive tumours appear to have conflicting clinic significance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study confirmed that Treg density correlated with adverse prognosis, consistent with earlier studies (Kono et al , 2006; Lu et al , 2011; Tao et al , 2012a). However, FoxP3-positive tumours appear to have conflicting clinic significance.…”
Section: Discussionsupporting
confidence: 93%
“…However, FoxP3-positive tumours appear to have conflicting clinic significance. Previous studies showed that Treg counts in sentinel lymph nodes were associated with lymph node metastasis (Lee et al , 2011), where increased tumour-infiltrating Tregs positively correlated with TNM stage (Yuan et al , 2010; Liang et al , 2011; Lu et al , 2011) and the proportion of Treg/CD4 was associated with GC recurrence (Kim et al , 2011). FoxP3-positive cancer cells were associated with pathological differentiation, T stage, and poor prognosis in tongue squamous cell carcinoma (Liang et al , 2011) and lymph node metastasis in non-small cell lung cancer (Dimitrakopoulos et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…28 Even if gastric cancer is frequently associated with Helicobacter pylori-induced gastritis, a high density of Foxp3 C cells is usually associated with a poor prognosis, as found in our present study and predominating the literature. [29][30][31][32] Only Haas et al found a relationship between high levels of Foxp3C cell tumor infiltration and improved prognosis in 52 patients bearing gastric adenocarcinomas of the cardia. 33 In the present work, we did not find a significant correlation between gastric cancer patient survival and the density of CD8 C or IL-17 C tumor-infiltrating cells.…”
Section: Discussionmentioning
confidence: 99%
“…It acts as a suppressor for tumor formation in normal intestinal epithelium while a promoter for tumor invasion, metastasis and tumor stem cell maintenance after cancer occurrence (Inman, 2011;Teicher, 2001). TGF-β1-509 C>T polymorphism may regulate gene expression, and are subsequently presumed to be correlated with risk of gastric cancer formation (Lu et al, 2011;Perera et al, 2010). Although many epidemiological studies regarding TGF-β1-509 C>T polymorphism on the risk of DTC have been conducted, the results varied and were conflicting because of various reasons, such as different participants' ethnicities and resident areas, sample size, environmental factors and diet habits.…”
Section: Discussionmentioning
confidence: 99%